Addition of Non-Official Public Transportation Fares in Palembang City: A Study of Ijārah Contracts and Contemporary Fiqh - Kartikasari, Yunia; Wijaya, Sandy (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines the practice of adding city transportation fares (angkot) outside the official provisions that occur in the KM 5 Palembang area, this is reviewed from the perspective of the ijārah contract in the fiqh muʿāmalah and its relevance in the context of contemporary fiqh. This practice often occurs without transparency and explicit agreement between the driver and passengers, raising questions regarding the validity of the lease-hire contract (ijārah) in transportation service transactions. This study uses a juridical-normative and sociological approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the practice of increasing rates outside of official provisions does not fully meet the principles and conditions of the validity of the ijārah contract, especially in the aspects of willingness (tarāḍī) and clarity of rewards (ujrah). From the perspective of contemporary fiqh, the practice also has the potential to contain elements of gharar and harm the service users. Therefore, stricter regulations and education on sharia economic law are needed to create justice and openness in transportation service transactions.